A minireview on nanofluids for automotive applications: Current status and future perspectives. (25th January 2023) - Patel, Jatin; Soni, Abhishek; Barai, Divya P.; Bhanvase, Bharat A.
Graphical abstract: Highlights: Nanofluids have superior thermophysical, rheological, and tribological properties. Nanofluids can be applied as radiator coolant, engine fuel, and engine lubricant. There exist several challenges for automotive applications of nanofluids. Recommendations for automotive applications of nanofluids are disclosed. Abstract: In view of the superior thermophysical, rheological, and tribological properties of nanofluids, they are applicable for heat transfer and lubrication in automobiles. Nanofluids in automobiles have possible applications such as a radiator coolant, engine lubricant, air conditioning system lubricant, engine fuel, brake fluid, and shock absorber. This review focuses on automotive applications of nanofluids. Details about the experimental reports on the various properties of nanofluids along with correlations for nanofluids have been specified. How nanofluids prove to be advantageous as well as the disadvantages of their use in automobiles are elaborated. Along with this, it emphasizes the challenges and future directions for nanofluids for each automotive application of nanofluids. It has been found that the stability of the nanofluids and the lack of sufficient data to provide proof hinder their way towards commercialization. Overall, there is still a lot of scope and need for research in nanofluid applications in the automotive area.